Impact of Work-Life Balance, Work Stress, Compensation on Turnover Intention and Job Satisfation of Gen-Z Employees - Ayanda Nur, Shanaz (Economic and Bussiness Faculty, Dr Soetomo University, 2025)
This study aims to determine the effect of work-life balance, work stress, and compensation on turnover intention mediated by job satisfaction. This research uses primary data from Generation Z employees. The sampling technique used purposive sampling which involved 100Gen-Z employees. The results showed that (1) work-life balance influence significantly on job satisfaction and turnover intention significantly, but job satisfaction cannot mediating work-life balance to turnover intention, (2) work stress has no effect significantly on job satisfaction and turnover intention and also job satisfaction cannot mediating the impact of work stress on turnover intention, (3) compensation influence job satisfaction and turnover intention, while job satisfaction can mediating the effect of compensation on turnover intention, and (4) gender cannot moderating the relation between job satisfaction and turnover intention